STUDENTS VOCABULARY AND PAIRS TEACHING - Halim Shanty (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This article is aimed at describing the use of pairs teaching in developing students vocabulary. Vocabulary plays an important role in learning English. It is a core component of language proficiency. In mastering English well, students should have sufficient vocabulary because vocabulary is needed in four language skills; they are listening, speaking, reading and writing. Those skills support each other. One of the methods that can be used to teach vocabulary is pairs teaching. Pairs teaching are a classroom activity in which the whole class is divided into groups. Pairs teaching as method which provides a great review and enables students to gather information from each other. The students not only silent in the class but they are sharing idea to get information especially sharing vocabulary. It was first organized as a theory by Scotsman Andrew Bell in 1795, and later implemented into French and English schools in the 19th century. Over the past 30-40 years, pairs teaching have become increasingly popular in conjunction with mixed ability grouping in public schools and an interest in more financially efficient methods of teaching.